Differential equations a modern approach with wavelets - Krantz, Steven G. (Steven George), 1951- ([Boca Raton] : CRC Press, 2020)
This new book from one of the most published authors in all of mathematics is an attempt to offer a new, more modern take on the Differential Equations course. The world is changing. Because of the theory of wavelets, Fourier analysis is ever more important and central. And applications are a driving force behind much of mathematics.This text text presents a more balanced picture. The text covers differential equations (both ordinary and partial), Fourier analysis and applications in equal measure and with equal weight. The Riemann integral is used throughout. We do not assume that the student knows any functional analysis. We likewise do not assume that the student has had a course in undergraduate real analysis. To make the book timely and exciting, a substantial chapter on basic properties of wavelets, with applications to signal processing and image processing is included. This should give students and instructors alike a taste of what is happening in the subject today.
OCLC-licensed vendor bibliographic record.
Keywords: Differential equations -- Textbooks; Wavelets (Mathematics) -- Textbooks; MATHEMATICS / Differential Equations